Optimising telemedicine in ophthalmology during the COVID-19 pandemic. (August 2022) - Patel, Shriji; Hamdan, Saif; Donahue, Sean
Ophthalmology, an outpatient surgical specialty, depends on regular in-person encounters to manage complex eye disease. The coronavirus disease 2019 (COVID-19) pandemic has brought about unprecedented challenges in how we take care of our patients. At Vanderbilt University Medical Center, we have gone to great lengths to implement expeditiously a telemedicine platform for safely and securely evaluating our patients during the pandemic. Since implementing live videoconference appointments in late March, 840 patients received ophthalmic care during a 12-week period among all subspecialties at the Vanderbilt Eye Institute. Of these, the majority (79.6%) were either return or postoperative visits. Live telehealth visits were more amenable to certain ophthalmic subspecialties, with paediatrics, neuro-ophthalmology and oculoplastics encounters making up 80.5% of all telemedicine visits. As demonstrated through this care model and our initial experience, live video telemedicine is a sustainable and safe care delivery approach to extend ophthalmic care delivery during the COVID-19 pandemic and even post pandemic.